Biological and clinical insights from a randomized phase 2 study of an anti-oncostatin M monoclonal antibody in systemic sclerosis. (18th May 2022) - Denton, Christopher P; del Galdo, Francesco; Khanna, Dinesh; Vonk, Madelon C; Chung, Lorinda; Johnson, Sindhu R; Varga, John; Furst, Daniel E; Temple, Jane; Zecchin, Chiara; Csomor, Eszter; Lee, Amy; et al.
Abstract: Objectives: The cytokine oncostatin M (OSM) is implicated in the pathology of SSc. Inhibiting OSM signalling using GSK2330811 (an anti-OSM monoclonal antibody) in patients with SSc has the potential to slow or stop the disease process. Methods: This multicentre, randomized, double-blind, placebo-controlled study enrolled participants ≥18 years of age with active dcSSc. Participants were randomized 3:1 (GSK2330811:placebo) in one of two sequential cohorts to receive GSK2330811 (cohort 1: 100 mg; cohort 2: 300 mg) or placebo s.c. every other week for 12 weeks. The primary endpoint was safety; blood and skin biopsy samples were collected to explore mechanistic effects on inflammation and fibrosis. Clinical efficacy was an exploratory endpoint. Results: Thirty-five participants were randomized to placebo ( n  = 8), GSK2330811 100 mg ( n  = 3) or GSK2330811 300 mg ( n  = 24). Proof of mechanism, measured by coordinate effects on biomarkers of inflammation or fibrosis, was not demonstrated following GSK2330811 treatment. There were no meaningful differences between GSK2330811 and placebo for any efficacy endpoints. The safety and tolerability of GSK2330811 were not favourable in the 300 mg group, with on-target, dose-dependent adverse events related to decreases in haemoglobin and platelet count that were not observed in the 100 mg or placebo groups. Conclusion: Despite a robust and novel experimental medicine approach and evidence of target engagement, anticipated SSc-related biologic effects of GSK2330811 were not different from placebo and safety was unfavourable, suggesting OSM inhibition may not be a useful therapeutic strategy in SSc. Trial registration number: ClinicalTrials.gov, NCT03041025; EudraCT, 2016-003417-95.